2018
DOI: 10.1103/physrevb.98.115413
|View full text |Cite
|
Sign up to set email alerts
|

Dirac nodal line in bilayer borophene: Tight-binding model and low-energy effective Hamiltonian

Abstract: Bilayer hexagonal borophene, which is bound together through pillars, is a novel topological semimetal. Using density functional theory, we investigate its electronic band structure and show that it is a Dirac material which exhibits a nodal line. A tight-binding model was constructed based on the Slater-Koster approach, which accurately models the electronic spectrum. We constructed an effective four-band model Hamiltonian to describe the spectrum near the nodal line. This Hamiltonian can be used as a new pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 59 publications
(64 reference statements)
1
17
0
Order By: Relevance
“…As shown in Table 6, as the layers increases, the number of interlayer B-B bonds increases rapidly from 3 Furthermore, the typical interlayer B-B bonds were selected to plot the ELF slice views to further understand the interlayer bonding natures of these multilayer BBP systems, as shown in Figure S22 and 8. The ELF of a 2-layer BBP system is mainly distributed over the middle region between two bonded interlayer boron atoms (B7-B8 and B10-B11 in Figure S22a and S22b, respectively), confirming the typical covalent features, which is in accordance with the case in previous studies [22,41,[43][44][45]. The ELF slice views for the B13-B14 bond (0.44, bond population; type (Ⅱ)) and B16-B17 bond (0.83, bond population; type (III)) of 3-layer BBP systems were plotted, as shown in Figure S22c and S22d, respectively.…”
Section: Electronic Structuressupporting
confidence: 91%
“…As shown in Table 6, as the layers increases, the number of interlayer B-B bonds increases rapidly from 3 Furthermore, the typical interlayer B-B bonds were selected to plot the ELF slice views to further understand the interlayer bonding natures of these multilayer BBP systems, as shown in Figure S22 and 8. The ELF of a 2-layer BBP system is mainly distributed over the middle region between two bonded interlayer boron atoms (B7-B8 and B10-B11 in Figure S22a and S22b, respectively), confirming the typical covalent features, which is in accordance with the case in previous studies [22,41,[43][44][45]. The ELF slice views for the B13-B14 bond (0.44, bond population; type (Ⅱ)) and B16-B17 bond (0.83, bond population; type (III)) of 3-layer BBP systems were plotted, as shown in Figure S22c and S22d, respectively.…”
Section: Electronic Structuressupporting
confidence: 91%
“…In contrast, these results are seen to be distinctly different from those of P 6 mmm-B and P 6̄- B , in which the Dirac bands have seldom in-plane orbital contributions because of their bilayer structures. 35,38…”
Section: Resultsmentioning
confidence: 99%
“…As one of the most active research fields, searching for preferable 2D nodal line semimetals is always ongoing. Although there are quite a few theoretical studies of 2D nodal line materials, 35,38,47–49 only Cu 2 Si and CuSe have been observed experimentally. 50,51 However, strictly speaking, Cu 2 Si and CuSe are not desirable in that their nodal loops are gapped by the sizable SOC.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…54 More interestingly, a novel topological state semimetal against the impurities is found in bilayer borophene, and the robust metallic is unaffected by the change of symmetry. 55 Such morphological stability and stubborn metallic character of the bilayer borophene render its prospective applications in electrode materials of LIBs with high storage ability and superb conductivity.…”
Section: ■ Introductionmentioning
confidence: 99%